(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
Inthisarticle, firstly, theloca lliterary criticismofallof Graham Greene’s collectionsofshortstories (54 stories) inrelation to his novelistic work is reviewed. It comprehendsively consists of their studies, and establishes the related concepts: ‘shortstory’, ‘novella’, and ‘story’. It excretes the groups of short stories written in satiric, humorous, model and plans approaches to their analysis.